Delay in diabetic retinopathy screening increases the rate of detection of referable diabetic retinopathy. Issue 4 (17th October 2013) - Scanlon, P. H.; Aldington, S. J.; Stratton, I. M.
Abstract Aims To assess whether there is a relationship between delay in retinopathy screening after diagnosis of Type 2 diabetes and level of retinopathy detected. Methods Patients were referred from 88 primary care practices to an English National Health Service diabetic eye screening programme. Data for screened patients were extracted from the primary care databases using semi‐automated data collection algorithms supplemented by validation processes. The programme uses two‐field mydriatic digital photographs graded by a quality assured team. Results Data were available for 8183 screened patients with diabetes newly diagnosed in 2005, 2006 or 2007. Only 163 with Type 1 diabetes were identified and were insufficient for analysis. Data were available for 8020 with newly diagnosed Type 2 diabetes. Of these, 3569 were screened within 6 months, 2361 between 6 and 11 months, 1058 between 12 and 17 months, 366 between 18 and 23 months, 428 between 24 and 35 months, and 238 at 3 years or more after diagnosis. There were 5416 (67.5%) graded with no retinopathy, 1629 (20.3%) with background retinopathy in one eye, 753 (9.4%) with background retinopathy in both eyes and 222 (2.8%) had referable diabetic retinopathy. There was a significant trend (P = 0.0004) relating time from diagnosis to screening detecting worsening retinopathy. Of those screened within 6 months of diagnosis, 2.3% had referable retinopathy and, 3 years or more after diagnosis, 4.2% had referable retinopathy. Conclusions The rate of detection of referable diabetic retinopathy is elevated in those who were not screened promptly after diagnosis of Type 2 diabetes.